Blood-brain barrier opening with focused ultrasound in Parkinson’s disease dementia - Carmen Gasca-Salas (Nature Portfolio, 2021)
Blood brain barrier (BBB) opening is being investigated as a therapeutic approach for neurodegenerative diseases. Here, the authors report the results of a phase I trial to evaluate the feasibility and safety of BBB opening of the right parieto-occipito-temporal cortex in Parkinson´s disease with dementia.